PENGEMBANGAN SISTEM EVALUASI DESAIN PRODUK BERBASIS ROTAN DENGAN PENDEKATAN REKAYASA KANSEI DAN ASSOCIATION RULES SYSTEM - Vonny Setiaries Johan; Sapta Rahardja; E Gumbira Said; Taufik Djatna (AGROINTEK, 2012)
In product development, it is very important for manufacturers to find out what the customer wants from the product. On the other hand, manufacturers do not know clearly about what the customer wants from the product. This study proposes an evaluation method of product design using Kansei engineering methods and association rules approach. Using rattan dining chair as the object, the chair design divided into five elements, which are backrest, seat, armrest, base and woven. In this study, Kansei words from customers such as beautiful, unique, innovative, comfortable, natural, modern, sturdy and simple can be translated in to element design.   Using the support and confidence values, if-then rules can be used as the basis for the assessment of rattan dining chairs